The Effects of Shale Oil and Gas Endowments on Regional Labor Markets - Chung, Seunghun; Hean, Oudom (International Journal of Energy Economics and Policy, 2022)
We analyze the effects of shale oil development on regional labor markets. By exploiting the exogenous geographic endowment of shale oil and gas, we find that shale endowments have differential impacts on workers in and out of the labor market. After introducing new shale technologies in 2006, shale oil and gas significantly increased the local share of high school graduates participating in the labor force. Yet, shale endowments decreased the percentage of nonworking college graduates who do not participate in the labor force. Our results suggest that shale oil and gas could increase the demand for high school graduates but create disamenities for college graduates who are not in the labor force.